STUDY OF THE ACHIEVEMENT OF PHYSICS LEARNING OUTCOMES OF STUDENTS IN HIGH SCHOOLS IN THE SOUTH TANGERANG REGION THROUGH THE TRIAL OF LKS BASED ON THE SCIENTIFIC APPROACH - Hertanti, Erina; Silvia, Risma Mega; Al-Afifah, Jaenab Athial (UIN Sunan Gunung Djati Bandung, 2025)
The research is purposed to study the physics result of learning achievement in the senior high school students in South Tangerang, through LKS trial-testing based on a scientific approach. The research was held in four senior high schools in South Tangerang. They are SMA Negeri 6 South Tangerang, SMA Al-Hasra Bojongsari Baru, SMA Negeri 1 South Tangerang, and SMA Dua Mei. It was conducted from May to August 2014. The research method used was pre-experimental, using a one-group pretest-posttest design. The sampling was done by purposive sampling technique. The hypothesis test used a statistical test of one-way analysis of variance. The result analysis or hypothesis test can gain a significance value